Pemodelan Dicision Tree Untuk Analisis Penjualan Barang Pada Koperasi Dwi Makmur Desa Menden - Junaidi, Muksan SAN; Valentika, Mia Nanda; Wibawa, Eka Satria (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2024)
The Dwi Makmur Menden Cooperative located in Mendenrejo Village, which is engaged in savings and loan businesses and goods stores. Service problems often arise in stores due to running out and delays in stock of goods. The purpose of this research is to produce a rule or rules between goods that are often sold simultaneously with classification techniques and to determine the level of consumer purchases in associations between product combinations. The research data is taken from the sale of goods for the 2020 period, where there are often problems with the availability of goods on stock cards. The decision tree algorithm from the rapidminer application will be used as a classification process tool. The results from the decision tree clearly show that the import results from selling prices that are categorized as in demand are sales of goods greater than (>) than 87250, while those categorized as not selling are sales of goods that are less than (<) than 87250. With unit prices less than (<) 75000 and the unit price is greater (>) than 75000.